Dose and local efficacy analysis of iodine-125 seed implantation therapy for lung tumors - Cao, Guohui; Chang, Xiaojing; Wang, Zeyang; Liu, Xiaoli; Xu, Ke; Wang, Juan; Zhang, Hongtao (Frontiers in Oncology, 2025)
ObjectiveTo explore the dose and local efficacy of iodine-125 seed implantation therapy for lung tumors.MethodsThe clinical data of 85 patients with lung tumors who underwent iodine-125 seed implantation therapy were retrospectively analyzed. The impact of prescription dose D90 (minimum peripheral dose received by the 90% target volume) on the local treatment effect six months after seed implantation was analyzed, and the critical value for predicting efficacy was determined. Factors affecting the local complete response (CR) rate six months after surgery were also analyzed.ResultsThe local control rate at six months after treatment was 89.41% (76/85), and the objective response rate (ORR) was 70.59% (60/85), with a CR rate of 31.76% (27/85). Patients with a post-procedure D90 > 140 Gy had a significantly higher local CR rate. Multivariate analysis revealed that post-procedure D90 and tumor size were independent prognostic factors for achieving CR six months after lung tumor seed implantation.ConclusionIodine-125 seed implantation therapy is effective for lung tumors. Tumor size (P = 0.0003) and post-procedure D90 (P = 0.0005) were found to be independent prognostic factors for achieving post-procedure CR after lung tumor seed implantation.